2006
DOI: 10.1038/sj.ijo.0803516
|View full text |Cite
|
Sign up to set email alerts
|

The thrifty ‘catch-up fat’ phenotype: its impact on insulin sensitivity during growth trajectories to obesity and metabolic syndrome

Abstract: The analyses of large epidemiological databases have suggested that infants and children who show catch-up growth, or adiposity rebound at a younger age, are predisposed to the development of obesity, type 2 diabetes and cardiovascular diseases later in life. The pathophysiological mechanisms by which these growth trajectories confer increased risks for these diseases are obscure, but there is compelling evidence that the dynamic process of catch-up growth per se, which often overlaps with adiposity rebound at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(169 citation statements)
references
References 94 publications
6
149
1
5
Order By: Relevance
“…Moreover, amino acid delivery immediately after birth does not match the high fetal protein intake (16). In addition, it has been suggested that catch-up growth may lead to a state of skeletal muscle insulin resistance, which seems to be strictly associated with an accelerated rate of deposition of fat mass rather than fatfree mass (FFM) (17). The adipose tissue appears to exert a specific control of thermogenesis, i.e., thermogenesis is suppressed by the depleted adipose fat stores during starvation, to spare energy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, amino acid delivery immediately after birth does not match the high fetal protein intake (16). In addition, it has been suggested that catch-up growth may lead to a state of skeletal muscle insulin resistance, which seems to be strictly associated with an accelerated rate of deposition of fat mass rather than fatfree mass (FFM) (17). The adipose tissue appears to exert a specific control of thermogenesis, i.e., thermogenesis is suppressed by the depleted adipose fat stores during starvation, to spare energy.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of being used in the skeletal muscle glucose is redistributed for lipogenesis and storage in the adipose tissue. This preferential "catch-up fat" can eventually lead to an increased adiposity that, in association with adipose tissue hyper-responsiveness and hyperinsulinemia, may represent an additional risk factor for the development of the metabolic syndrome in young adulthood (17). On the basis of these experimental studies, the rapid catch-up fat shown by the late preterm infants could be partially explained by the fact that the infants enrolled in this study were relatively "underfed" in the first days of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More direct evidence for the occurrence of preferential catch-up fat early in life can be derived from a recent longitudinal study of body composition -assessed by dual energy x-ray absorptiometry (DEXA) scan -in infants between the ages of 2 and 5 years born SGA in Spain. 32 A re-analysis of these data 30 reveals that already between ages of 2 and 4.5 years, children born SGA gained more total body fat and less lean tissue, and hence a markedly higher ratio of fat mass to lean tissue mass, than children born AGA, despite similar gains in weight and BMI (Figure 1). By about 4 years of age, those children born SGA had greater total adiposity and abdominal fat, and showed lower insulin sensitivity, than children born AGA.…”
Section: The Insulino-resistant 'Catch-up Fat' Phenotypementioning
confidence: 99%
“…4,5 Although there is a general agreement that modest weight loss has beneficial health effects in obese patients, 6 there are some hypotheses that suggest that weight cycling could be damaging particularly for CVD risk. 7,8 However, studies investigating the effect of weight variability on CVD risk have shown controversial results. Some studies indicated that the overall weight trend had a greater deleterious effect on CVD risk than weight fluctuation (WF) (that is the WF effect was not significant after adjustment for weight change), [9][10][11] whereas others concluded that WF had an independent effect.…”
Section: Introductionmentioning
confidence: 99%